Conceptual Metaphors in British Foreign Secretary’s Twitter Discourse Involving Ukraine - Kapranov, Oleksandr (Respectus Philologicus, 2016)
This article presents a qualitative study of conceptual metaphors identified in Twitter discourse involving Ukraine by the current British Foreign Secretary Phillip Hammond. The study further described in this article involves a corpus of Hammond’s tweets associated with Ukraine, which is subsequently juxtaposed with Hammond’s online articles and speeches involving Ukraine in order to elucidate whether or not there are Twitter-specific conceptual metaphors in Hammond’s Twitter discourse associated with Ukraine. The results of the data analysis reveal that Hammond’s short messages on Twitter, or tweets, associated with Ukraine are embedded in conceptual metaphors ‘Ukraine’s future EU Membership as a Journey’, ‘UK as a Nurturant Parent’, ‘EU as a Nurturant Parent’, ‘Country as a Friend Helping Ukraine’ and ‘Russia as the EU’s OTHER’. Identical conceptual metaphors have been found in Hammond’s online non-Twitter discourse involving Ukraine. These findings are further presented and discussed in the article.
Keywords: Conceptual Metaphor; Political Discourse; Twitter; The UK; Ukraine